Metabolic profiling of Apostichopus japonicus body wall exposed to a typical type of PBDEs: potential health risks and impact on sea cucumber health - Ding, Kui; Zhuo, Pengji; Ge, Meiling; Liao, Xiaomei; Mo, Jing; Liu, Shilin; Xu, Qinzeng; Zhang, Xuelei (Frontiers in Marine Science, 2023)
Sea cucumbers are cultivated mainly for their valuable body wall. Polybrominated diphenyl ethers are common persistent pollutants in sea waters with known impacts on aquatic animals nonetheless not yet studied for the body wall of sea cucumbers.We studied the impact of 2,2',4,4'-tetrabromodiphenyl ether (BDE-47) on metabolic changes in the body wall of Apostichopus japonicus. The results demonstrated that BDE-47 exposure induced significant alterations in the metabolic profiles of the body wall. A total of 95 102 metabolites in the 0.1 10.0 µg/L BDE-47 treated group were altered significantly, and various disrupted metabolic pathways were identified and characterized. The identified metabolites and metabolic pathways were mainly involved in lipid metabolism, energy metabolism, immunity, oxidative stress, inflammation, and neurotoxicity. The findings of our study may provide valuable 2,2',4,4'-Tetr abr omodiphenyl Ether (BDE-47) 删除[丁]: